Relations between Sequences and Selection Properties - D. Djurcic; Lj. D. R. Kocinac; M. R. Žižovic (Abstract and Applied Analysis)
We consider the set 𝕊 of sequences of positive real numbers and show that some subclasses of 𝕊 have certain nice selection and game theoretic properties.